THE EFFECTIVENES OF ETANOL EXTRACT, PARTITION N-HEKSANA, AND CROMATHOGRAPHY FRACTION OF MOMORDICA CHARANTIA L. TO LOWER BLOOD GLUCOSE LEVEL - Dewinda, Ni Luh Putu Kusuma Clara; Suartha, I Nyoman; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2017)
This study aims to determine the effectiveness of the ethanol extract, partition n-hexane, and chromatography fractions Momordica charantia L . in lowering blood glucose levels in experimental diabetic male rats.  This study used 25 male rats were divided into five treatment groups P 0 (negative control), P 1 (positive control), P 2 (ethanol extract), P 3 (partition n-hexane), and P 4 (chromatographic fraction) the variable observed glucose levels blood for 21 days. Blood glucose levels were analyzed on days -1, 0, 4, 11, 18. The bill, which is used in the form of a completely randomized design (CRD). The data obtained and analyzed by using Split in Time. The results showed of giving chromatographic fractions bitter melon 50 mg / kg body weight can reduce blood glucose levels in hyperglycemic rats better than the ethanol extract 200 mg / kg body weight and partition n-hexane 50 mg / kg body weight.